Análisis de los principales efectos de la política agropecuaria del ecuador en el periodo 2010 2020 - Ochoa Mendieta, Alexandra Cecibel (Machala : Universidad Técnica de Machala, 2022)
The role of the agricultural sector in the world is fundamental, food security and industry depend on agriculture, hence its importance, which is why this research has set itself the objective: to analyze the main effects caused by agricultural policy during the period 2010 – 2020; For this, a bibliographical review related to topics such as agrarian policy and economic policy in Ecuador was used; Among the main agricultural policies implemented are the agricultural projects for the good living of the rural population, agricultural credits, agricultural insurance, minimum support prices and the national storage unit, which have been very useful for the development of activities. agriculture and its sustainability over time; After analyzing the main agricultural policies implemented during the last 10 years in Ecuador, it has been possible to demonstrate as a main point the continuity of some policies such as agricultural projects for good rural living, agricultural loans and agricultural insurance, this has been positive for the country, its economy and mainly for agricultural producers.
El rol del sector agropecuario en el mundo es fundamental, la seguridad alimentaria y la industria dependen de la agricultura, de aquí su importancia, es por esto que en esta investigación se ha planteado como objetivo: analizar los principales efectos ocasionados por la política agropecuaria durante el periodo 2010 – 2020; para esto se recurrió a la revisión bibliográfica relacionada con temas como política agraria y política económica en Ecuador; entre las principales políticas agrícolas implementadas se detallan los proyectos agropecuarios por el buen vivir de la población rural, créditos agrícolas, seguro agrícola, precios mínimos de sustentación y la unidad nacional de almacenamiento; luego de analizar las principales políticas agrícolas implementadas durante los últimos 10 años en Ecuador, se ha podido evidenciar como principal punto la continuidad de algunas políticas como los proyectos agropecuarios por el buen vivir rural, créditos agropecuarios y seguro agrícola, esto ha sido positivo para el país, su economía y principalmente para los productores agrícolas.
Keywords: SEGURIDAD ALIMENTARIA; AGRICULTURA; POLÍTICA; PROYECTOS AGROPECUARIOS